(2x+9(2))+(1x-5(2))=50

Simple and best practice solution for (2x+9(2))+(1x-5(2))=50 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+9(2))+(1x-5(2))=50 equation:


Simplifying
(2x + 9(2)) + (1x + -5(2)) = 50

Multiply 9 * 2
(2x + 18) + (1x + -5(2)) = 50

Reorder the terms:
(18 + 2x) + (1x + -5(2)) = 50

Remove parenthesis around (18 + 2x)
18 + 2x + (1x + -5(2)) = 50

Multiply -5 * 2
18 + 2x + (1x + -10) = 50

Reorder the terms:
18 + 2x + (-10 + 1x) = 50

Remove parenthesis around (-10 + 1x)
18 + 2x + -10 + 1x = 50

Reorder the terms:
18 + -10 + 2x + 1x = 50

Combine like terms: 18 + -10 = 8
8 + 2x + 1x = 50

Combine like terms: 2x + 1x = 3x
8 + 3x = 50

Solving
8 + 3x = 50

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 3x = 50 + -8

Combine like terms: 8 + -8 = 0
0 + 3x = 50 + -8
3x = 50 + -8

Combine like terms: 50 + -8 = 42
3x = 42

Divide each side by '3'.
x = 14

Simplifying
x = 14

See similar equations:

| 188.9024=6.28r^2+20.069r | | -4n+6(5n-1)=72 | | 5y-6=-29 | | 64.8+18t+4.9t^2=0 | | ((2)2x+9)+((2)1x-5)=50 | | x^2-6-5=0 | | 975=25N | | x-378=0 | | 4(x+4)=5(2x-4) | | 2X^2=3-3X | | ax+7=12-bx | | -5(8+7x)-2x=145 | | 6(1+2m)+m=71 | | (8n+56)-(2n+14)= | | 7r^2+10=80 | | 2x+9(2)+1x-5(2)=50 | | 6(2x+7)=78 | | 1672.992=2*3.14*51.84+2*3.14*7.2*h | | 15319=525+.0575(15319-30000) | | 6(r-5)=-66 | | y=-x(-6) | | 3z^2+17+20=0 | | 3x+2x+5x+5=40 | | 10(x-4)=50 | | 7-7x=7x+5x | | -5(5x-3)+4x=120 | | (5x+6)(7x+7)= | | 2a^2-4=126 | | bx-1=63 | | X-y=c(X) | | 4x+14=9x-35 | | 2y^2+6y+5=0 |

Equations solver categories